Pengaruh Audit Internal terhadap Penerapan Good Corporate Governance pada PT.Bank Mandiri Persero Tbk KCP Sudirman Palembang - Pratiwi, Nurlely; Indriani, Poppy (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of internal audit on the implementation of good corporate governance at PT. Bank Mandiri (Persero) Tbk KCP Sudirman Palembang. Good corporate governance is the dependent variable in this study, while internal audit is the independent variable. The sample in this study was 31 employees who were obtained using a non-probability sampling technique. This type of research is causal associative, where there is a causal relationship between the dependent and independent variables. The data collection techniques used were interviews and questionnaires using a multiple linear regression analysis approach through IBM SPSS version 21 software. The results of this study indicate that the implementation of internal audit has a significant influence on good corporate governance with a significant value of alpha 0.000 (0.000 <0.05).